APPLICATION OF ELECTRYC DRILLINGS AT BUILDING SLOPING-DIRECTED MINING HOLES - Коцкулич, Ярослав Степанович; Ставичний, Євген Михайлович; П'ятківський, Станіслав Анатолійович; Коцкулич, Євген Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The indexes of the boring drilling of the sloping-directed mining holes are resulted with application of electric drillings. The perspective ways of perfection of constructions of electric drillings and technologies of their application are outlined.